Why EQF and the Future of EQF - Alfredo Soeiro (2013)
Good morning! We are 4356 Kms away but I hope that we can communicate. Thank you Prof. Zaytseva for the invitation. It is a plesure and an honour to be presenting this subject. I have chosen this title since it is important to understand the reasons why I think EQF was created and what I think will its future. Most of the slides are from the European Commission official documents.